Motives to take up bridging courses by nurses – preliminary study - Pilewska-Kozak, Anna B.; Łepecka-Klusek, Celina; Kozak, Łukasz; Bałanda-Bałdyga, Bałanda-Bałdyga (Nursing in the 21st Century, 2012)
MOTIVES TO TAKE UP BRIDGING COURSES BY NURSES – PRELIMINARY STUDYIntroduction. According to EU directives, Polish nurses have had a chance to complete education within the system of bridging courses; many of them have taken advantage of that modality.Aim. The paper aims to establish motives to take up bridging courses by nurses and to find out the plans concerning their future career.Material and methods. A survey was conducted in the group of 90 nurses, aged 40.9 + 3.7 years mean, who took up bridging courses in February 2012. They were surveyed by a questionnaire.Results. The respondents were choosing from 20 different motives. Since they were often repeated, the answers were divided into three groups: group 1 – aspirations, group 2 – completion of knowledge and acquisition of new skills and group 3 - financial aspects. The most often chosen motives were from group 1 and least chosen were those from group 3. Only 13 respondents (14.4%) declared that they are willing to continue education (M.A. courses), the majority of them (67 respondents, 74.4%) were unable to define their plans, and 10 (11.1%) respondents stated they were not going to continue further education.Conclusions. The nurses have various motives to take up bridging courses. Professional aspirations and completion of education are the most frequent among them. A decisive majority are unable to specify their views concerning further education plans.